Pemenuhan Hak dan Kewajiban Orang Tua terhadap Anak dalam Keluarga Tuna Susila Perspektif Undang-Undang Perlindungan Anak Nomor 23 Tahun 2002 : (Studi Kasus Wilayah di Poncol Kecamatan Semarang Utara Kota Semarang) - Rizqi Dhafin Hibatullah; Tri Wahyu Hidayati (International Forum of Researchers and Lecturers, 2025)
The aim of this research is to determine the pattern of parenting practices of immoral parents towards children in the Poncol Region, and to determine the parenting practices of immoral parents towards children in the Poncol Region from the perspective of the Child Protection Law Number 23 of 2002 concerning Child Protection. This research is field research (Field Research). Field research is research that focuses on the context of individuals, groups, organizations, social situations and social interactions. Meanwhile, this research uses a normative juridical approach with the provisions of Child Protection Law Number 23 of 2002. This research uses two data sources, namely primary data in the form of data from interviews with research objects and secondary data in the form of Child Protection Law Number 23 of 2002 and official documents related to this research. The results of the research show that the parenting patterns of families with disabled students in the Poncol area according to the Child Protection Law number 23 of 2002, some of them treat children correctly without taking or abusing the child's rights. So it can be concluded that there are still some who have not carried out their obligations as parents to care for, educate and protect their children. So, when parents do not fulfill their obligations, the child does not get full rights.